The effects of mixed-age classes in Sweden - Elly-Ann Johansson; Erica Lindahl (Institute for Labour Market Policy Evaluation (IFAU), 2008)
Mixed-aged classes (MA-classes) are a common phenomenon around the world. In Sweden, these types of classes increased rapidly during the 1980:s and 1990:s. But the scientific evidence of the benefits of MA-classes is not convincing. In this paper, we estimate the effect of attending an MA-class during grades 4-6 on students' cognitive skills. Using a unique survey with information on students, parents and teachers, we are able to control for many factors that could otherwise bias the results. We find a negative effect on the short-run cognitive skills, as measured by grade 6 cognitive tests.
Keywords: I21; J31; 330; Education; mixed-age classes; multi-grade classes; Allgemeinbildende Schule; Schüler; Altersgruppe; Kognition; Schweden